2013
DOI: 10.1111/vco.12024
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood abnormalities and bone marrow infiltration in canine large B‐cell lymphoma: is there a link?

Abstract: Official guidelines do not consider bone marrow (BM) assessment mandatory in staging canine lymphoma unless blood cytopenias are present. The aim of this study was to find out if blood abnormalities can predict marrow involvement in canine large B-cell lymphoma. BM infiltration was assessed via flow cytometry. No difference was found between dogs without haematological abnormalities and dogs with at least one. However, the degree of infiltration was significantly higher in dogs with thrombocytopenia, leucocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…Interestingly, 50% of the dogs with bone marrow involvement (with < 5% to > 20% neoplastic lymphocytes) lacked hematologic abnormalities, such as thrombocytopenia, leukocytosis, or lymphocytosis. In agreement with our results, these authors found that bone marrow disease was also present in dogs without hematologic abnormalities, suggesting that bone marrow evaluation should be included in routine staging . Strategies for evaluating bone marrow disease in human patients with lymphoma are still evolving .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, 50% of the dogs with bone marrow involvement (with < 5% to > 20% neoplastic lymphocytes) lacked hematologic abnormalities, such as thrombocytopenia, leukocytosis, or lymphocytosis. In agreement with our results, these authors found that bone marrow disease was also present in dogs without hematologic abnormalities, suggesting that bone marrow evaluation should be included in routine staging . Strategies for evaluating bone marrow disease in human patients with lymphoma are still evolving .…”
Section: Discussionsupporting
confidence: 91%
“…The implementation of more sensitive tests such as flow cytometry would probably improve the ability of detecting neoplastic cells. A recent study used flow cytometry of blood and bone marrow samples to determine the presence of neoplastic cells in dogs with large B‐cell lymphoma . Interestingly, 50% of the dogs with bone marrow involvement (with < 5% to > 20% neoplastic lymphocytes) lacked hematologic abnormalities, such as thrombocytopenia, leukocytosis, or lymphocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, this proportional error has only a tenuous clinical relevance, since it affects only high infiltration values, which are uncommon in canine LBCL (11,12) and far from the prognostically relevant cut-off of 3% (11). Indeed, only a slight proportional error in BM dilutions was found.…”
Section: Discussionmentioning
confidence: 88%
“…Although causes for this slight error are not neat to the authors, this may be associated to preanalytical factors, such as manual dilutions preparation, or to the presence of stromal or adipose cells either in the LN or in the BM sample that were counted by the hematology analyzer but were not included in the FC gates. However, this proportional error has only a tenuous clinical relevance, since it affects only high infiltration values, which are uncommon in canine LBCL (11,12) and far from the prognostically relevant cut-off of 3% (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation